Roles of viable but non-culturable state in the survival of Campylobacter jejuni - Santos, Leticia Silva; Rossi, Daise Aparecida; Braz, Raquelline Figueiredo; Fonseca, Belchiolina Beatriz; Guidotti–Takeuchi, Micaela; Alves, Rosiane Nascimento; Beletti, Marcelo Emílio; Almeida-Souza, Hebreia Oliveira; Maia, Larissa Prado; Santos, Paula de Souza; de Souza, Jéssica Brito; Melo, Roberta Torres de (Frontiers in Cellular and Infection Microbiology, 2023)
The emergence of Campylobacter jejuni worldwide and the recent international requirements in its control instigated us to qualitatively and quantitatively estimate the time required for the acquisition of the VBNC form in 27 strains of C. jejuni, characterise morphological aspects, determine its adaptive and invasive potential and perform comparative metabolomic evaluation. Extreme stress promoted the complete acquisition of the VBNC form in a mean time of 26 days, depending on the strain. Starting from an average initial count of 7.8 log CFU/mL, the first four days determined the greatest average reduction of the culturable form of 3.2 log CFU/mL. For the remaining days, this reduction was constant and equivalent to 0.33 log CFU/mL. The image analyses showed a transition from the typical viable form (VT) to the VBNC form. RT-PCR identified a character maintained in the VBNC form only for p19 and in 59.3% of the VBNC strains for the ciaB gene. The average inoculation of 1.8 log CFU/mL of C. jejuni VBNC into primary chicken embryo hepatocyte cells promoted the occurrence of apoptosis processes significantly after 24 hours of contact by one of the strains tested. For another VBNC strain, we identified weak action in necrosis and apoptosis processes, but this behaviour did not differ from that found in the culturable form and in the positive control, probably due to the low number of inoculated cells. In C. jejuni VBNC, we detected higher expression of metabolites linked to protective and adaptation mechanisms and of volatile organic precursor compounds indicative of metabolism interruption. In the typical viable form of C. jejuni, we identified high levels of compounds related to the exponential and stationary growth phase of the bacterium. The oscillations in the time of acquisition of the VBNC form together with the presence of transcripts for ciaB and p19, the identification of cell lysis and metabolites that ensure the maintenance of the pathogen alert to the fact that C. jejuni VBNC remains virulent and adapted to stress, which makes evident the potential danger of this latent form, which is not detectable by official methodologies.